Sex, gender and family – the Christian contribution to an ethic of intimate relationships - De Lange, F (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
“Among all the changes going on in the world, none is more important than those happening in our personal lives – in sexuality, relationships, marriage and the family. There is a global revolution going on in how we think of ourselves and how we form ties and connections with others. It is a revolution advancing unevenly in different regions and cultures, with many resistances” (Giddens, 2003: 51).